Sertifikat Ganda Pada Proyek Pembangunan Rumah Susun - Septivany Christa Perdana (Fakultas Hukum Universitas Pancasila, 2018)
The aim of the land registration is to ensure the legal certainty for land tenure within Indonesia territory. Besides that, land registration is conducted to prevent the land tenure dispute. The land registration process results the land certificate proving the land tenure for specified person or party. In practice, the legal certainty matter would deal with several obstacles, among others, the double land certificates problem. This study examines the double land certificates problem in Kedung Waringin Village, Bojonggede District, Bogor City. This study shows several factors causing the double land certificates problem, among others, the internal weakness inside National Land Agency Bogor Branch Office, and to overcome such problem, it has conducted alternative dispute resolution effort, namely negotiation, mediation, and facilitation.